Proceedings of the 2015 ACM on International Conference on Multimodal Interaction 2015
DOI: 10.1145/2818346.2820759
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Silent Participant

Abstract: Estimating a silent participant's degree of engagement and his role within a group discussion can be challenging, as there are no speech related cues available at the given time. Having this information available, however, can provide important insights into the dynamics of the group as a whole. In this paper, we study the classification of listeners into several categories (attentive listener, side participant and bystander). We devised a thin-sliced perception test where subjects were asked to assess listene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…The fourth phase consisted of the students describing their projects' impact on society, and in the fifth and final phase they were asked to collaboratively come up with a joined project proposal. In a previous study, on the same corpus [13], it was found that third party observers could distinguish between at least three distinct types of listeners; an attentive listener, a side-participant, and a bystander. It was also found that the frequency of backchannel tokens was related to the perception of listener categories.…”
Section: Corpusmentioning
confidence: 95%
“…The fourth phase consisted of the students describing their projects' impact on society, and in the fifth and final phase they were asked to collaboratively come up with a joined project proposal. In a previous study, on the same corpus [13], it was found that third party observers could distinguish between at least three distinct types of listeners; an attentive listener, a side-participant, and a bystander. It was also found that the frequency of backchannel tokens was related to the perception of listener categories.…”
Section: Corpusmentioning
confidence: 95%
“…As Echeverria [10] provided a thorough survey of quantitative approach of analyzing group communications, recent studies exploited motion sensors and computer vision technologies to recognize human behaviors and automatically estimate the characteristics of the participants and meeting groups. With the goal of estimating the level of engagement of silent participants in multiparty communication, Oertel et al [28] proposed classifying group members into attentive listeners, side participants, and bystanders. They used verbal and nonverbal backchannels as prediction features.…”
Section: Related Work 21 Feedback Response In Human Communicationmentioning
confidence: 99%
“…The recognition models using the features mentioned above were initially based on heuristic approaches [27,33,43]. Recent methods are based on machine learning techniques such as support vector machines (SVM) [18,23,36,42], hidden Markov models [30], and convolutional neural networks [41]. In this study, we focus on behaviors when the user is listening to system speech, such as backchannels, laughing, head nodding, and eye-gaze.…”
Section: B) Engagement Recognitionmentioning
confidence: 99%
“…In this case, another approach is based on 'wisdom of crowds' where many annotators are recruited. Eventually, the annotations were integrated using methods such as majority labels, averaged scores, and agreed labels [18,22,23]. In our proposed method, the different views of the annotators are taken into account.…”
Section: B) Engagement Recognitionmentioning
confidence: 99%
See 1 more Smart Citation